Empirical model for Darrieus-type tidal current turbine induced seabed scour. (1st September 2018) - Sun, Chong; Lam, Wei Haur; Cui, Yonggang; Zhang, Tianming; Jiang, Jinxin; Guo, Jianhua; Ma, Yanbo; Wang, Shuguang; Tan, Teng Hwang; Chuah, Joon Huang; Lam, Su Shiung; Hamill, Gerard
Highlights: Empirical model is proposed for Darrieus-type tidal current turbine induced scour. Experiments are carried out associated with three dimensional printed turbines. Extents of scour hole are studied at various tip clearance and radius of turbines. Scour profiles are classified as two types with different tip clearance. Abstract: Tidal current turbine has attracted many attentions, but the impact of Darrieus-type tidal current turbine on the seabed scour process still remains unclear. This work aims to propose an empirical model, which can be used to predict the maximum scour depth against different tip clearance and rotor radius. The study also presents the scour profiles along centreline of turbine by using the proposed empirical equations. A series of three-dimensional printed turbine models were placed in a circulating water flume to investigate the scour profiles. The results suggest that the scour depth increases with the decrease of tip clearance. When the turbine is installed very close to seabed, the scour process is live bed scour with the collapse of the slant bed. Under this kind of condition, the maximum scour depth will not further increase with the continuous decrease of tip clearance. The current experimental results propose that the maximum scour depth is about 80% deeper than scour depth around single pile. The maximum scour depth increases firstly and then decreases with the increase of rotor radius. Based on experimental results, an empirical model of Darrieus-type tidal current turbine induced seabed scour is proposed to predict the maximum scour depth and scour profiles along centreline of turbine.